2022
DOI: 10.15280/jlm.2022.12.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Level of Physical Activity Knowledge of Medical Students in a Brazilian University

Abstract: Background Physical inactivity is a major global public health problem, with a large impact on morbidity and mortality. For this reason, knowledge and advice on physical activity (PA) should be common to all health professionals. In this context, the role of physicians stands out, because they act in the first contact and have a high potential in addressing this issue and its impact on health promotion, prevention, and treatment in chronic diseases. This study aims to observe the level of physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…However, these findings had statistically insignificant association (p-value 0.210) (Table 13). Relevant to mention that this finding is supported by previous research that found no relation between knowledge and physical activity [25].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…However, these findings had statistically insignificant association (p-value 0.210) (Table 13). Relevant to mention that this finding is supported by previous research that found no relation between knowledge and physical activity [25].…”
Section: Discussionsupporting
confidence: 84%
“…This may be in line with their background knowledge. And medical students' knowledge on physical activity was demonstrated in previous findings [25]. However, 40% of those who practice faced significant interference due to academic load, 35% faced no none while 25% reported occasional interference (p-value 0.063) (Table 12), which was not statistically significant.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The majority of the participants were aware of the advantages of regular PA as well as the necessity of PA as a preventive and control measure of non-communicable diseases which were consistent with a previous study. [13] The respondents did, however, show a lack of understanding when questioned whether stretching is considered an aerobic exercise, whether 4-5 days per week of PA is the minimum requirement for receiving health benefits or whether prolonged participation in endurance sports might lead to fractures in bones and the body. A comparable study among American medical students showed they lacked knowledge of the specifics of exercise.…”
Section: Discussionmentioning
confidence: 99%
“…In the realm of medical education, participation of undergraduate medical students in physical activity was extensively studied internationally [12][13][14][15][16][17][18][19][20][21][22][23][24] Yet scientists and medical educators are still assessing various aspects pertaining to their involvement, understanding and active promotion, aiming towards improvement at all domains [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. This sheds light on the additional importance related to future doctor's role in physical activity directed healthcare promotion, which remains suboptimal [43][44][45].…”
Section: Introductionmentioning
confidence: 99%